2004
DOI: 10.1590/s0100-879x2004000200011
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Ki-67 antigen in 159 pituitary adenomas using the MIB-1 monoclonal antibody

Abstract: Pituitary adenomas sometimes show rapid growth and recurrence, and about one third invade the structures surrounding the sella turcica. In an attempt to determine aggressive behavior at an early stage, we used the MIB-1 antibody to identify the Ki-67 antigen. The present study was designed to evaluate pituitary adenomatous tissue in terms of secretion and proliferation and to correlate the Ki-67 index with hormone phenotype and invasive behavior. Material from 159 patients submitted to one or more resections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 28 publications
3
51
2
6
Order By: Relevance
“…20) Some studies also demonstrated a correlation between MIB-1 labeling index and re-growth or recurrence, 9,14,30,32) but other studies found no such correlations. 5,13,24,27) These discrepancies and differences between estimates of the threshold MIB-1 labeling index may be attributable to variations in the definition of recurrence or progression. 26) Another possible source of differences or discrepancies is the method used to count the labeled cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20) Some studies also demonstrated a correlation between MIB-1 labeling index and re-growth or recurrence, 9,14,30,32) but other studies found no such correlations. 5,13,24,27) These discrepancies and differences between estimates of the threshold MIB-1 labeling index may be attributable to variations in the definition of recurrence or progression. 26) Another possible source of differences or discrepancies is the method used to count the labeled cells.…”
Section: Discussionmentioning
confidence: 99%
“…8,18) Various attempts have been made to establish markers that correlate with the clinical behavior of pituitary adenomas, such as invasion, recurrence, or malignancy. 1,2,5,[7][8][9][10][12][13][14][15]17,[19][20][21][22][23][24][27][28][29][30][31][32][33] Among the available methods of growth fraction determination, Ki-67 is a reliable marker for growth fraction determination of various specific cell cycle antigens. 1,12,32) Ki-67 is a protein which reacts with a …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the other types (ACTH cell adenomas in Nelson's syndrome, inactive ACTH cell adenomas, FSH/LH cell adenomas, and TSH cell adenomas) demonstrated invasion of surrounding structures in the majority of tumors investigated (82-100%; Table 3) (22). Invasive pituitary adenomas are generally characterized by a higher Ki-67 proliferation index (13,14). In addition, invasive adenomas may demonstrate p53-positive nuclei, which were found to be absent in enclosed adenomas (14,23,24).…”
Section: Invasiveness As a Marker Of Pituitary Adenomasmentioning
confidence: 99%
“…Mastronardi et al examined 103 pituitary gland adenoma patients and found the Ki-67 proliferation index to be a useful marker for the invasion character of pituitary tumors (33). There are some other studies that support this study (21,22,26,40). Kawamato et al managed another study regarding the relationship between invasion and Ki-67 proliferation index and found no correlation (24).…”
Section: Resultsmentioning
confidence: 59%